2006
DOI: 10.1590/s0043-31442006000400008
|View full text |Cite
|
Sign up to set email alerts
|

A review of medicinal plant research at the University of the West Indies, Jamaica, 1948-2001

Abstract: This review summarizes research carried out on Jamaican medicinal plants at the Faculty of Pure and Applied Science, The University of the West Indies (UWI), Mona, Jamaica, between 1948 and. The plants identified as being medicinal are listed along with their folk use and a summary of the scientific research done at UWI leading to the identification of natural products (NPs) and determination of their bioactivity. Natural product research on Jamaican medicinal plants began with the inception of UWI in 1948, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 40 publications
0
57
0
Order By: Relevance
“…Earlier studies confirmed the insecticidal effects of these plants species: B. ferruginea [45]; B. sapida [15,36,[50][51][52][53]; and K. senegalensis [54][55][56][57][58][59]. Acetone extract of K. senegalensis showed the lowest LC 50 and the biggest toxicity ratio, consequently the most toxic on D. porcellus.…”
Section: Psychementioning
confidence: 71%
See 1 more Smart Citation
“…Earlier studies confirmed the insecticidal effects of these plants species: B. ferruginea [45]; B. sapida [15,36,[50][51][52][53]; and K. senegalensis [54][55][56][57][58][59]. Acetone extract of K. senegalensis showed the lowest LC 50 and the biggest toxicity ratio, consequently the most toxic on D. porcellus.…”
Section: Psychementioning
confidence: 71%
“…In fact, the antifungal [12], antibacterial [13], and insect antifeedant [14] properties of leaf extract of K. senegalensis have been demonstrated. The fruit of ackee (B. sapida) has insecticide properties [15], whereas the antimicrobial properties of leaves and bark extract of B. ferruginea have been proved by Sahu et al [16]. In order to develop an integrated approach to control and lay the groundwork for the development of a botanical insecticide, experiments should be carried out to assess the insecticidal and repellent effects of these three plants species on D. porcellus.…”
Section: Introductionmentioning
confidence: 99%
“…Several drugs that are currently available in the international market were the result of exhaustive scientific and systematic explorations of the traditional claims of the plants and ethnopharmacology. Regardless of the global rise in scientific investigation on medicinal plants, only small numbers of plant-derived bioactive compounds have reached the market, locally or internationally, due to their evidencebased therapeutic potential (Mitchell & Ahmad, 2006). The reasons for a low number of plant-based drugs reaching the market could be associated to the lack of endeavors taken to determine or validate the evidence related to the safety of the respective plant, which, in turn, is mistakenly assumed to be safe due to their plant-based and naturally occurring facts (Yob et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…"Bush teas" were an early research focus of the then University College of the West Indies (3)(4)(5), resulting in the identification of a new disease known as venoocclusive disease and produced warnings on the potential toxic effects of bush teas (6). But despite warnings to the public and the availability of modern medicines (7), bush teas remain quite widely used and some teas may be introduced as early as in the first six months of life (8). The early work did not address trace elements which have become of interest because of naturally elevated levels of heavy metals in some Jamaican soils (9) and foods (10).…”
Section: Introductionmentioning
confidence: 99%